Phenotypic effects on male risk-taking behavior in Leptuca beebei from field experiments at Playa El Agallito, Chitre, Panama: Efecto fenotípico en la toma de riesgos por Leptuca beebei en experimentos de campo en Playa El Agallito, Chitré, Panamá - Lombardo, Roberto (Revista Científica Vida Natural, 2025)
Risk-taking behavior in Leptuca beebei was studied through field experiments conducted at Playa El Agallito, Chitré, Panama. This study aimed to determine whether larger males or those with pillar structures take greater risks when courting females and whether female size affects male risk-taking behavior. Females exhibiting mate-searching behavior were tethered 30 cm in front of randomly selected courting males, both with and without pillars. Male behavior was observed using binoculars, recording the maximum distance traveled from their burrow and whether they intercepted the female. Results indicate that male size and pillar presence did not significantly affect the distance traveled or the likelihood of intercepting the tethered female. Males traveled an average of 18.8 cm from their burrows, but this distance was not influenced by female size. Instead, males' risk-taking behavior may have been influenced by factors such as predation risk and potential burrow loss, rather than female size. The findings suggest that the dangers of leaving their burrows outweigh the benefits of courting distant or larger females. Thus, their behavior is influenced more by ecological risks and reproductive costs than by the characteristics of potential mates.